Sympathetic Innervation Promotes Arterial Fate by Enhancing Endothelial ERK Activity. Issue 5 (19th August 2016) - Pardanaud, Luc; Pibouin-Fragner, Laurence; Dubrac, Alexandre; Mathivet, Thomas; English, Isabel; Brunet, Isabelle; Simons, Michael; Eichmann, Anne
Abstract : Rationale : Arterial endothelial cells are morphologically, functionally, and molecularly distinct from those found in veins and lymphatic vessels. How arterial fate is acquired during development and maintained in adult vessels is incompletely understood. Objective : We set out to identify factors that promote arterial endothelial cell fate in vivo. Methods and Results : We developed a functional assay, allowing us to monitor and manipulate arterial fate in vivo, using arteries isolated from quails that are grafted into the coelom of chick embryos. Endothelial cells migrate out from the grafted artery, and their colonization of host arteries and veins is quantified. Here we show that sympathetic innervation promotes arterial endothelial cell fate in vivo. Removal of sympathetic nerves decreases arterial fate and leads to colonization of veins, whereas exposure to sympathetic nerves or norepinephrine imposes arterial fate. Mechanistically, sympathetic nerves increase endothelial ERK (extracellular signal-regulated kinase) activity via adrenergic α1 and α2 receptors. Conclusions : These findings show that sympathetic innervation promotes arterial endothelial fate and may lead to novel approaches to improve arterialization in human disease. Abstract : Supplemental Digital Content is available in the text.